Potential role of interleukin 28B-gene polymorphism and natural immune enhancer treatment response in chronic HCV patients (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
HCV infection is a major health problem in Egypt. Studies using safe natural products Blue green® tablet showed its antiviral effect. Polymorphisms in the interleukin-28B (IL28B) gene are associated with outcomes from infection with HCV. The rationale of the present study is to evaluate the potential role of interleukin 28B gene polymorphism (IL28B) and natural immuneenhancer treatment response in chronic HCV patients. This study included 100 chronic HCV patients. Patients were classified into two groups: Group I, fifty patients with cirrhosis and advanced liver disease. Patients were unfit INF/ Ribavirin: Group II, fifty patients who refused INF/Ribavirin. Patients were treated with combination of natural products of Blue green® tablet (4 tablets daily which equivalent to 100 mg AFA/30 kg BW), vitamin D, tea spoon field paste of black seeds, olive oil and honey. Alanine Aminotransferase (AST), Aspartate Aminotransferase (ALT), complete blood count (CBC) were measured in the two groups. Detection of HCV-RNA level by quantitative PCR was done before & after 3, 6, 12 and 18 months of treatment. Genomic DNA extracted from all the 100 patient’s blood samples was analyzed for the rs12979860 SNPof IL28B using a real-time polymerase chain technique incorporating SYBR Green. The results showed that, the activities of hepatic marker enzymes (AST and ALT), complete blood pictures (Hb, WBCs and Platelets), HCV RNA PCR, IL 28-B gene polymorphism were non-significantly (p>0.05) differences when compared untreated patients (Group I) and treated patients (Group )were CC genotype before treatment was 8 (34%) & was 13 (26%) after treatment, CT genotype before treatment was 26 (52%) & was 28 (56%) after treatment, TT genotype before treatment was 7 (14%) & was 9 (18%) after treatment. Also, there were non-significant (p>0.05) differences between responder & non-responder in treated patients. In conclusion, the treatmentwith natural immune enhancer in chronic HCV patients showed no significance correlation with IL 28 gene polymorphism